Pengaruh Penerapan Pembelajaran Berorientasi Aktivitas Siswa Dan Motivasi Belajar Terhadap Prestasi Belajar Siswa Kelas IX SMP Negeri 3 Kabupaten Pamekasan - Sutanti, Tiwuk (Metafora: Education, Social Sciences and Humanities Journal, 2019)
This research related to Implementation of instruction based students’ activities and Students’ learning Motivation toward students’ learning achievementt of Ninth Grade Students State Junior High School 3 Pamekasan regency . The students’ learning achievementt is influenced by Implementation of instruction based students’ activities. Additionally it is influenced by Students’ learning Motivation. Good and regularly Implementation of instruction based students’ activities brings a positive effect on the students’ learning achievement and a high learning motivation in teaching will increase the students achievement.            The purpose of this research is (1) to describe  Implementation of instruction based students’ activities toward students’ learning achievement. (2) to describe the significant influence of the Students’ learning Motivation toward students’ learning achievement . (3) to describe the significant influence of Implementation of instruction based students’ activities and Students’ learning Motivation simultaniously toward students’ learning achievement.            The design of this research is descriptive quantitative. The subject of the research is Ninth Grade Students of State Junior High School 3 Pamekasan. The data collecting technique is by giving some questionnaires. Data analyzing technique used patial and multi-regression computerized SPSS 17.00 program for windows. The Result and the discussion as follows:  a) There is a significant influence on the Implementation of instruction based students’ activities  (X1) toward students’ learning achievement is about 0,312. b) There is a significant influence on the Students’ learning Motivation (X2) toward students’ learning achievement is about 0,062 by the significanct level 0,000, on t-account, that means smaller than 0,05. It can be concluded that X1 and X2 are very significant. c) There is a significant influence on the Implementation of instruction based students’ activities and Students’ learning Motivation simultaneously toward students’ learning achievement is about 17,617 by the significanct level 0,000, on F-account, that means smaller than 0,05. It can be concluded that X1 and X2 are very significant toward Y.